MARINE SPONGE Aaptos suberitoides, IT’S POTENTIAL SOURCE OF NATURAL ANTIBACTERIAL FOR CONTROLLING Vibrio harveyi ON TIGER SHRIMP (Penaeus monodon) CULTURE - Rosmiati Rosmiati; Andi Parenrengi; Emma Suryati (Indonesian Aquaculture Journal, 2015)
The study aims to isolate and identify the natural antibacterial compounds potential from Aaptos suberitoides for Vibrio harveyi control on tiger shrimp (Penaeus monodon) culture. The agar diffusion method using paper discs was used to determine the antibacterial activity of extracts (diethyl ether (DEE), butanol (BUE) and aqueous (HOE) and compounds successfully isolated against Vibrio harveyi. Findings showed that the antibacterial activity was concentrated in BUE with the inhibition zone of 17.2±0.1 mm. Meanwhile, two other extracts (DEE and HOE) did not exhibit any antibacterial activity against V. harveyi. From the active BUE, it was successfully isolated two compounds giving a strong anti-vibrio activity with the inhibition zone of 22±0.1 mm. The IR, 1H, 13C, COSY, HMQC, HMBC, and MS spectrum analysis indicated that both active compounds identified as aaptamine (1) and 9-demethyloxyaaptamine (2). The study suggested that marine sponge A. suberitoides may have potential compounds source for controlling of V. harveyi on tiger shrimp culture.